The role of IT projects within the strategy: How effectively do we use them? - Szabó Károly; Szabó László (Journal of Engineering Management and Competitiveness)
It is a general trend that the role of projects is increasingly appreciated in the life of individual organizations. We have come to the point in the last decade where certain organizations use this method for their entire operation, while large companies implement their priority developments only with project management methods. The project management knowledge is becoming progressively essential also in the case of smaller businesses nowadays as they come into contact with projects through their partners or their own experiences. Although the methodology is constantly spreading and growing, so far, there have been just a few scientific results about where IT projects are located in the organization's goal-system and how they are related to the corporate or organizational strategy. Accordingly, the basic goals of the IT projects will be examined in the framework of the current research, and the questions about that, are these goals related to the corporate strategy and how effective are the individual companies using their IT projects?